What is the Significance of a Part Per Million? - Frederick M. Fishel; Mark Mossler (EDIS, 2005)
The health effects of toxic substances are related to their doses—the amount of exposure to the toxic substance. The greater the dose, the more likely it is to affect our health, but some chemicals can cause toxicity even at very small doses. Therefore, it's very important to understand how doses are described, how they relate to one another, and what these doses represent when compared to other substances were exposed to every day. This document is PI-79, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2005.